Tantangan Kualitas Air: Evaluasi Kolam dan Rawa (Cemaran Kimia, Fisika dan Biologi) di KHDTK Kemampo Sumatera Selatan - Tri Wulandari (Journal of Biotropical Research and Nature Technology, 2023)
This study aims to evaluate the surface water quality of ponds and swamps in the Kemampo Banyuasin Special Purpose Forest Area (KHDTK) Palembang. Water quality is vital for human life and ecosystems. Therefore, this study focused on physical, chemical and biological parameters to assess the level of contamination and cleanliness of the water. The research methods included field surveys and experiments, as well as laboratory testing. Physical parameters such as temperature, colour, and odour were measured directly, while chemical (pH, Cd, Pb, Fe, and Cu) and biological (Coliform and Escherichia coli) parameters were analysed at the Integrated Laboratory of UIN Raden Fatah Palembang. The chemical test method used Atomic Absorption Spectrophotometer (SSA), while the biological parameters were measured by Most Probable Numbers (MPN). The results showed variations in temperature between stations, with the highest value reaching 30°C. Water was generally brown or turbid in colour and odour. Coliform content ranged from 46 to 2004 MPN/100mL, while chemical parameters showed variations in pH between 5.25 to 5.55. Concentrations of heavy metals such as Cd, Pb, Fe and Cu were also measured, with the water exceeding the water quality standard for sanitary hygienic purposes (Class I), but still meeting the Class III quality standard for irrigating crops or other uses requiring similar water quality. These findings emphasise the need for better protection and management of the water.